P360 Inflammatory microheterogeneity in ulcerative colitis: implications for microscopic assessment of disease activity. (25th January 2019) - Harpaz, N; Ballentine, S; Sands, B E; Colombel, J-F; Ko, H M
Abstract: Background: UC is classically a continuous inflammatory disorder. Biopsies to assess disease activity, whether for clinical purposes or to monitor therapeutic responses in drug trials, are typically sampled 1 or 2 per colonic segment on the assumption of homogeneous inflammation throughout targeted regions. Nonetheless, data are lacking to validate this assumption. Methods: We retrospectively evaluated inflammation in histological sections of ascending (AC) and rectosigmoid (RS) colon from colectomy specimens of 18 random adults with UC. A series of consecutive 2 mm diameter (100×) microscopic mucosal fields was scored by 2 pathologists using the Nancy Histological Index (NHI) to generate a score of 0–4 per field. The Robarts modification of the Geboes Index was used to score 4 individual histological parameters: chronic inflammation, lamina propria neutrophils, intraepithelial neutrophils, erosions. Median NHI scores and proportions of discrepant fields, that is, those with higher or lower scores, were determined for each series. Demographic data, disease durations, indications for surgery, and current drug therapies were obtained from electronic records. Results: The patients spanned a broad spectrum of clinical characteristics (Table 1). Mean 100× fields assessed per segment were 70.4 ± 24.1. Table 2 shows the breakdown of NHI scores from the AC and RS. Median AC scores exceeded median RS scores in 3/18 series (17%) series and the reverse occurred in 7/18 series (39%). The proportions of discrepant fields were similar in the AC and RS, 31.7 vs. 33.4%, respectively, and their distributions are shown (Figure 1). The range of NHI scores in the AC and RS was ≥3 in 11/18 (61%) and 12/18 (67%) series, respectively. Microheterogeneity was observed in all 4 histological parameters. Conclusions: Inflammation in the colectomies of patients with active UC requiring colectomy exhibits both microheterogeneity and AC-RS discordance. The design of biopsy protocols for clinical studies and therapeutic drug trials must take these preanalytical factors into account. Optimum biopsy densities should be determined by means of prospective studies of endoscopic biopsies.